Şeriat ve Tasavvuf Bağlamında Din-Çevre İlişkisi Üzerine Bir Değerlendirme / The Relationship between Religion and Environment in the Context of Shari'a and Sufism - YÜCER, Hür Mahmut; Yılmaz, Sinan (Journal of History Culture and Art Research, 2013)
Din-çevre ilişkisi, dinî araştırmalarda çok sayıda çalışmaya konu olmuştur. Bu çalışma ise, diğerlerinden farklı olarak, din çevre ilişkisinin sadece şeriat bağlamında değil, aynı zamanda tasavvuf bağlamında da ele alınabileceğini ortaya koymaktadır. Çalışmanın birinci bölümünde din-çevre ilişkisi şeriat bağlamında ele alınmış, din-fiziki çevre, din-sosyal çevre ve din-beden ilişkisi incelenmiştir. Ayrıca, din-beden ilişkisinin çevre bağlamında değerlendirilmesi konusunda önemli açılımlar getirilmiştir. İkinci bölümde ise, tasavvuf bağlamında din-çevre ilişkisine değinilmiş, ilk bölümde ele alınan konuların tamamı tasavvuf düşüncesi bağlamında yeniden ele alınmıştır. Bununla birlikte, çevre konusunda aslında şer’î ve tasavvufi düşüncenin birbirlerinden farklı argümanlar üretmediği ortaya konulmaya çalışılmıştır. A Sociological Approach to the Relationship between Religion and Environment in the Context of the Shari'a and Sufism The relationship between religion and the environment has been discussed in numerous studies. However this study, unlike the others, presents that the relationship between religion and the environment could be dealt with not only in the context of the Shari’a but also in the context of Sufism. In the first part of the study, the relationship between religion and the environment is dealt with in the context of the Shari’a. In this part, the relation between religion and the physical environment, religion and the social environment and religion and the body has been examined. In this part, significant developments over examination of the relation between religion and the body in the context of the environment have been provided. In the second part, the relationship between religion and the environment is touched upon in the context of Sufism. In this part, all the issues that have been addressed in the first part have been re-examined in the context of the thought of Sufism. Meanwhile, it has been endeavored to prove that the thought of the Shari’a and that of Sufism have not produced different arguments regarding with the environment.